Clinical microbial laboratory investigation - Shahdan, Intan Azura (2015)
Microorganisms universally attach to surfaces and produce extracellular polysaccharides, resulting in the formation of a biofilm. Biofilms pose a serious problem for public health because of the increased resistance of biofilm-associated organisms to antimicrobial agents and the potential for these organisms to cause infections in patients with indwelling medical devices. The roles of biofilms in infection, including the bloodstream and urinary tract infections, will be presented in this talk. The various collection methods for sampling and transporting biofilm-associated organisms will also be shared in the presentation. In summary, this talk provides a clear understanding on the roles and physiological aspects of biofilms that would enhance the clinical decision-making process.